Punk Sociology / by David Beer. - Beer, David (London : Palgrave Macmillan UK : Imprint: Palgrave Pivot, 2014., 2017)
This book explores the possibility of drawing upon a punk ethos to inspire and invigorate sociology. It uses punk to think creatively about what sociology is and how it might be conducted and aims to fire the sociological imaginations of sociologists at any stage of their careers, from new students to established professors.